Deprivation and psychopathology in the Fragile Families Study: A 15‐year longitudinal investigation. (14th May 2020) - Miller, Adam Bryant; Machlin, Laura; McLaughlin, Katie A.; Sheridan, Margaret A.
Abstract : Background: Early adversity consistently predicts youth psychopathology. However, the pathways linking unique dimensions of early adversity, such as deprivation, to psychopathology are understudied. Here, we evaluate a theoretical model linking early deprivation exposure with psychopathology prospectively through language ability. Methods: Participants included 2, 301 youth (47.5% female) enrolled in the Fragile Families and Child Wellbeing Study. We include data from assessment points at ages 1, 3, 5, 9, and 15. Latent factors for deprivation and threat were modeled from multiple indicators at ages 1 and 3. Youth language ability was assessed at Age 5. Indicators of psychopathology were assessed at ages 5, 9, and 15. A structural equation model tested longitudinal paths to internalizing and externalizing psychopathology from experiences of deprivation and threat. Results: Deprivation from birth to Age 3 was associated with an indirect effect on internalizing and externalizing symptoms in early childhood (Age 5), later childhood (Age 9), and adolescence (Age 15) via language ability in early childhood (Age 5). Early threat exposure was associated with increased internalizing and externalizing psychopathology across all ages. There was no significant indirect effect from threat to psychopathology via language ability. Conclusions: The effects of deprivation on psychopathology during early childhood, late childhood, and adolescence are explained, in part, through early childhood language ability. Results provide insight into language ability as a possible opportunity for intervention.